Designing for people. - Dreyfuss, Henry, ....- (New York : Allworth, 2003)
CHAPTER 1: The Early Days CHAPTER 2: Joe and Josephine CHAPTER 3: How the Designer Works CHAPTER 4: The Importance of Testing CHAPTER 5: THROUGH THE BACK DOOR CHAPTER 6: Rise in the Level of Public Taste CHAPTER 7: The Telephone CHAPTER 8: Land, Sea, and Air CHAPTER 9: The Open Road CHAPTER 10: Design in Unexpected Places CHAPTER 11: Working for the Government CHAPTER 12: The Five-Point Formula CHAPTER 13: Relationship of Designer to Client CHAPTER 14: That Sordid Subject Money CHAPTER 15: Not by Design CHAPTER 16: Why Are Barns Painted Red? CHAPTER 17: Profile of an Organization CHAPTER 18: Re-Appraisal